Strategi Pengelolaan Tanah Kas Desa dalam Mewujudkan Desa Mandiri di Desa Wunut - Muhammad Aniq Fadhilah; Setiowati; R. Deden Dani Saleh; Aristiono Nugroho (Sekolah Tinggi Pertanahan Nasional, 2026)
Village administration plays a vital role in national development, aligning with the 6th Asta Cita and the Village Law. However, the management of village treasury lands generally remains hindered by a lack of innovation and integrity. In contrast, Wunut Village in Klaten Regency has successfully optimized its treasury land into a productive tourism sector. This qualitative research aims to analyze Wunut Village's management strategies and their impact on achieving